Labour Law in Fisheries and Recommendations for Vietnam - Cuong, Do Viet; Lan Anh, Nguyen Thi; Phuong Thuy, Nguyen Thi (VNU Journal of Science: Legal Studies, 2025)
The adoption of modern technology in fisheries has both empowered workers The adoption of modern technology in fisheries has both empowered workers and necessitated new labour standards. labour standards. Moreover, Vietnam’s participation in new-generation free trade agreements requires the country to improve its labour standards in this sector in order to access trade incentives. This paper examines the alignment of the International Labour Organization’s Work in Fishing Convention, 2007 (No. 188) with existing Vietnamese law and assesses its implications for Vietnam. Based on this assessment, the paper offers recommendations to enhance the legal protection of fishers’ rights and to promote sustainable fisheries development in Vietnam.